Pathway analysis of the transcriptome and metabolome of salt sensitive and tolerant poplar species reveals evolutionary adaption of stress tolerance mechanisms - Janz, Dennis (BioMed Central, 2010)
BACKGROUND: Populus euphratica is a salt tolerant and Populus × canescens a salt sensitive poplar species. Because of low transcriptional responsiveness of P. euphratica to salinity we hypothesized that this species exhibits an innate activation of stress protective genes compared with salt sensitive poplars. To test this hypothesis, the transcriptome and metabolome of mature unstressed leaves of P. euphratica and P. × canescens were compared by whole genome microarray analyses and FT-ICR-MS metabolite profiling. RESULTS: Direct cross-species comparison of the transcriptomes of the two poplar species from phylogenetically different sections required filtering of the data set. Genes assigned to the GO slim categories 'mitochondria', 'cell wall', 'transport', 'energy metabolism' and 'secondary metabolism' were significantly enriched, whereas genes in the categories 'nucleus', 'RNA or DNA binding', 'kinase activity' and 'transcription factor activity' were significantly depleted in P. euphratica compared with P. × canescens. Evidence for a general activation of stress relevant genes in P. euphratica was not detected. Pathway analyses of metabolome and transcriptome data indicated stronger accumulation of primary sugars, activation of pathways for sugar alcohol production, and faster consumption of secondary metabolites in P. euphratica compared to P. × canescens. Physiological measurements showing higher respiration, higher tannin and soluble phenolic contents as well as enrichment of glucose and fructose in P. euphratica compared to P. × canescens corroborated the results of pathway analyses. CONCLUSION: P. euphratica does not rely on general over-expression of stress pathways to tolerate salt stress. Instead, it exhibits permanent activation of control mechanisms for osmotic adjustment (sugar and sugar alcohols), ion compartmentalization (sodium, potassium and other metabolite transporters) and detoxification of reactive oxygen species (phenolic compounds). The evolutionary adaptation of P. euphratica to saline environments is apparently linked with higher energy requirement of cellular metabolism and a loss of transcriptional regulation.